The effects of supplementing growing-finishing pig diets with carnitine and(or) chromium on growth and carcass characteristics - J W Smith II; B T Richert; K Q Owen; J R Bergstrom; W B Nessmith Jr; S A Blum; Jim L Nelssen; Robert D Goodband; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1996)
Eighty crossbred gilts (initially 83 lb)were used to examine the effects of 50 ppm carnitine and(or) 200 ppb chromium from chromium nicotinate on growth performance and carcass characteristics. In this trial, adding carnitine and(or) chromiun1 to the diets of high-lean growth finishing gilts did not increase carcass leanness. However, the combination of carnitine and chromium improved the color characteristics of the longissimus muscle.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Feed efficiency; Carnitine; Chromium